Analysis on thin sheet metal feeding characteristic by a servo roll feeder - Mohamad Zulhisyam, Mohd Razmi (2013)
This thesis was carried out to analyse thin sheet metal feeding characteristic by a servo roll feeder. Although servo roll feeding has been seen to be very successful in conventional sheet metal forming, no significant effort has been made to enable the application of this technology to micro sheet metal forming. A metal strip in micron size is very fragile, and it may be severely deformable if an inappropriate feeding facility is deployed. A model of feeder was created and simulation was further conducted to analyse the performance of servo roll feeder in term of accuracy and repeatability during feeding process of thin sheet metal. Several parameters were changed during simulation to acquire more data about servo roll feeder performance. The analysed showed that many factors affect the feed process in term of accuracy such as feed frequencies, feed distances and materials thickness.